Nitrogen Deprivation-Induced Production of Volatile Organic Compounds in the Arachidonic-Acid-Accumulating Microalga Lobosphaera incisa Underpins Their Role as ROS Scavengers and Chemical Messengers - Kumari, Puja; Cna’ani, Alon; Didi-Cohen, Shoshana; Tzin, Vered; Khozin-Goldberg, Inna (Frontiers in Marine Science, 2020)
The green microalga Lobosphaera incisa accumulates long-chain polyunsaturated arachidonic acid sequestered in triacylglycerols under nitrogen (N)-starvation conditions. Many of L. incisa’s physiological and metabolic responses to N-starvation have been previously investigated. However, the temporal dynamics of the volatile organic compounds (VOCs) under different N availability and their role in L. incisa stress responses have yet to be elucidated. Here, we investigated the VOC profiles of L. incisa to reveal their emission patterns, and proposed their physiological roles under N-starvation. Using gas chromatography-mass spectrometry, 42 and 19 VOCs were identified in the algal biomass (AVOCs) and in the medium (MVOCs), respectively, belonging to alkanes, alkenes, benzenoids, esters, fatty alcohols, fatty aldehydes, fatty acids (FAs), FA esters, ketones, and terpenoids; most of these are the oxidative products of FAs or photosynthetic pigment degradation. The discriminant AVOCs and MVOCs produced under N-starvation were identified by principal component analyses and hierarchical clustering. A significant treatment- and time-dependent increase in volatile FAs and their oxidative products was observed in the algal biomass and medium under N-starvation as compared to N-replete controls, following a similar pattern as reactive oxygen species (ROS) production. This suggests that VOCs may be involved in ROS scavenging. Despite the increase in total VOCs, terpenoids and alkenes decreased significantly with N-starvation duration, along with chloroplast degradation. Transcriptomic data supported the VOC patterns and revealed the upregulation of genes involved in fatty aldehyde, fatty alcohol, and ketone synthesis, including lipoxygenase, thioesterase, and fatty acyl CoA reductase, along with a decrease in the expression of genes putatively implicated in alkene biosynthesis. Several VOCs were identified as potential biotechnological targets, and their putative biosynthetic pathways were proposed, which could be genetically manipulated to enhance the yields of high value products. We conclude that VOCs may play an important role in stress metabolism, ROS scavenging, and the amelioration of oxidative stress under N-starvation. Also, VOCs released in the medium may communicate the signal to neighboring cells, thus priming them to adjust their metabolic activities to adapt to N-starvation conditions, indicating that the function of VOCs as chemical signaling messengers is conserved from microalgae to higher plants.